630 Management and Outcomes of Primary Central Nervous System Lymphoma – Time to Improve the Patient Pathway. (4th May 2021) - Norrington, M; Kumar, S; Islim, A; Smith, J; Husband, D; Mills, S; Jenkinson, M
Abstract: Introduction: The clinical and radiological presentation of PCNSL is diverse. Biopsy is required prior to commencing oncological therapy. Steroids administration or inconclusive histopathology may delay diagnosis. This study aimed to assess outcomes of patients managed under clinical oncology and haematology, and investigate factors related to survival. Method: Retrospective cohort study (2004-2019) of 104 patients. Univariate analysis, using Kaplan Meier curves and multivariate Cox regression analysis were performed. Results: Median WHO performance status was 1. 12 patients (11.5%) required repeat biopsy. 40 cases were managed under oncology, 25 males (median age 67 years; IQR 60-71). Median time from imaging to diagnosis (TTD) was 18 days (range 8-227). Median time from diagnosis to treatment (TTT) was 19 days (range 3-63). Median overall survival (OS) was 5 months (95% CI 0-15.6). 61 cases were managed under haematology, 32 males (median age 65 years; IQR 54-71). Median TTD was 25 days (range 10-233). Median TTT was 14 days (range 2-96). Median OS was 5 months (95% CI 2.1-7.9). No significant prognostic indicators of OS were identified on multivariate analysis. Conclusions: PCNSL carries a poor prognosis regardless of treatment team. The wide range in time to treatment suggests that the management pathway needs streamlining to improve outcomes.